2022
DOI: 10.1021/acssynbio.1c00626
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Aminoacyl-tRNA Synthetase Engineering for Genetic Code Expansion in Yeast

Abstract: Protein expression with genetically encoded noncanonical amino acids (ncAAs) benefits a broad range of applications, from the discovery of biological therapeutics to fundamental biological studies. A major factor limiting the use of ncAAs is the lack of orthogonal translation systems (OTSs) that support efficient genetic code expansion at repurposed stop codons. Aminoacyl-tRNA synthetases (aaRSs) have been extensively evolved in Escherichia coli but are not always orthogonal in eukaryotes. In this work, we use… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 80 publications
3
40
0
Order By: Relevance
“…Thus, our finding highlights the importance of applying selective pressure or phenotypic screening to identify cells with genomic rearrangements subjected to the SCRaMbLE system for a broader range of applications, as demonstrated in previous studies 32,33 . We also envision that the recombination frequency mediated by GCE-SCRaMbLE would be further enhanced by improving the suboptimal incorporation efficiency of OMeY into Cre enzyme via the engineering of LeuOmeRS/tRNA CUA pair 34 and eukaryotic release factor 1 (eRF1) that competes with unnatural amino acid insertion in response to stop codons 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our finding highlights the importance of applying selective pressure or phenotypic screening to identify cells with genomic rearrangements subjected to the SCRaMbLE system for a broader range of applications, as demonstrated in previous studies 32,33 . We also envision that the recombination frequency mediated by GCE-SCRaMbLE would be further enhanced by improving the suboptimal incorporation efficiency of OMeY into Cre enzyme via the engineering of LeuOmeRS/tRNA CUA pair 34 and eukaryotic release factor 1 (eRF1) that competes with unnatural amino acid insertion in response to stop codons 35 .…”
Section: Discussionmentioning
confidence: 99%
“…For the Ec LeuRS/tRNA Leu pair, we used the polyspecific aaRS variant LeuOmeRS with a T252A mutation in its editing domain and employed the ncAA O -methyl-L-tyrosine ( 1 ; OmeY) as a substrate (Wu et al, 2004). For the Ec TyrRS/tRNA Tyr pair, we employed a polyspecific aaRS variant, T2RS5, identified through our high-throughput screening and used it with the ncAA p -propargyloxyl-L-phenylalanine ( 2 ; OPG) as a substrate (Stieglitz and Van Deventer, 2022). Lastly, for the PylRS/tRNA Pyl pair, we used the M. alvus PylRS with the ncAA N ε - Boc-L-Lysine ( 3 ; BocK) as a substrate (Stieglitz et al, 2022) (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous engineering strategies are known to augment stop codon readthrough, including single-gene deletions, whole-genome synthesis, and engineering various components of the translation machinery (DeBenedictis et al, 2021; Dunkelmann et al, 2021; Gan et al, 2017; Sanders et al, 2022; Stieglitz and Van Deventer, 2022; de la Torre and Chin, 2021; Zackin et al, 2022). Prior work from our group has shown that the use of single-gene knockout strains of S. cerevisiae can enhance ncAA incorporation efficiencies in response to the TAG codon for a range of OTSs and ncAAs (Potts et al, 2020; Stieglitz et al, 2021; Zackin et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations